Maternity In Couples Of Women: Reformulating The Heteronormative And Biological Relationship - Ivan Fedya (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
Motherhood in female same-sex couples challenges two important aspects in the construction of western par-enthood: on the one hand, heteronormativity; and on the other, the emphasis on biological ties. The aim of this work is to analyze how these families confront their motherhood attending to such restrictive and exclusive situations. Qualitative research, based on semi-struc-tured interviews, was conducted with 28 women who had planned their motherhood in a same-sex relation-ship. It may be concluded that female same-sex couples have to face some obstacles that are related to the heter-onormative and biological construction of parenthood.